Experimental and theoretical study of Co sorption in clay montmorillonites. (28th March 2018) - Gil Rebaza, A V; Montes, M L; Taylor, M A; Errico, L A; Alonso, R E
Abstract: Montmorillonite (MMT) clays are 2:1 layered structures which in natural state may allocate different hydrated cations such as M-nH2 O (M = Na, Ca, Fe, etc) in its interlayer space. Depending on the capability for ion sorption, these materials are interesting for environmental remediation. In this work we experimentally study the Co sorption in a natural Na-MMT using UV-visible spectrometry and XRD on semi-oriented samples, and then analyze the sorption ability of this clay by means of ab initio calculation performed on pristine MMT. The structural properties of Na-MMT and Co-adsorbed MMT, and the hyperfine parameters at different atomic sites were analyzed and compared with the experimental ones for the first, and for the case of the hyperfine parameters, presented for the first time for the last. The theoretical predictions based on total energy considerations confirm that Co incorporation replacing Na is energetically favorable. Also, the basal spacing d001 experimentally obtained is well reproduced.